Typology of Cocoa Value Chain Governance in West Sulawesi - Astina Astina; Siti Jahroh; Anna Fariyanti (International Journal of Agriculture System, 2019)
This paper discusses the value chain in cocoa marketing activities that occur in cocoa farmers to cocoa bean processing institutions. The typological approach is carried out to find out the relationships that are established in each chain starting from the farmers as the first chain (producers) to the processing institutions. An efficient marketing process is one of the objectives of cocoa marketing activities.  Value chain governance can illustrate typological coordination patterns that are related to each actor and show the type or type of governance type of each chain involved in marketing cocoa beans. Value chain governance (VCGs) is used to (1) identify the value chain and (2) determine the type of governance that is established in the cocoa market. So that we can know the conditions and types of governance that occur in the marketing of cocoa from the farmer to the final consumer. The method used is the analyze of VCGs by selecting a sample in a snowball sampling and calculating based on existing variables (complexity, codified, and capability). The results showed that through the VCGs approach which resulted in (1) there are 3 value chains with types of governance in cocoa marketing activities and (2) there are 3 value chains with types of governance, namely the value chain 1 (farmers–collectors-exporters) shows the Market type, value chain 2 (farmers-exporters) in Relational type, and value chian 3 in Hierarchy type (farmers-processing). Market type occurs if the value of complexity in low score, codification and capability gets a high score, Relational occurs if complexity and capability are in high value and the codification value is low, and Hierarchy occurs when the complexity is high but the codification and capability are low.